Abstinence and abstinence-only education - Ott, Mary A. (Curr Opin Obstet Gynecol, 2007)
PURPOSE OF REVIEW: To review recent literature on medical accuracy, program effectiveness, and ethical concerns related to abstinence-only policies for adolescent sexuality education. RECENT FINDINGS: The federal government invests over 175 million dollars annually in ‘abstinence-only-until-marriage’ programs. These programs are required to withhold information on contraception and condom use, except for information on failure rates. Abstinence-only curricula have been found to contain scientifically inaccurate information, distorting data on topics such as condom efficacy, and promote gender stereotypes. An independent evaluation of the federal program, several systematic reviews, and cohort data from population-based surveys find little evidence of efficacy and evidence of possible harm. In contrast, comprehensive sexuality education programs have been found to help teens delay initiation of intercourse and reduce sexual risk behaviors. Abstinence-only polices violate the human rights of adolescents because they withhold potentially life-saving information on HIV and other STIs. SUMMARY: Federal support of abstinence-only as an approach to adolescent sexuality education is of much concern due to medical inaccuracies, lack of effectiveness, and the withholding and distorting of health information.